2019
DOI: 10.1161/res.125.suppl_1.454
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 454: Plasticizer Interaction With the Heart: Chemicals Used in Plastic Medical Devices Can Interfere With Cardiac Electrophysiology

Abstract: Background: Phthalates are employed as plasticizers in the manufacturing of flexible, plastic medical products. Patients can be subjected to high phthalate exposure through contact with plastic medical devices. We aimed to investigate the cardiac safety and biocompatibility of mono-2-ethylhexyl phthalate (MEHP), a phthalate with documented exposure in intensive care patients. Methods and Results: Optical mapping of transmembrane voltage and pacing studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 0 publications
2
30
0
Order By: Relevance
“…Accordingly, high spatial resolution images (in the described setup 1240 x 1024 total, or 620 x 512 per channel, 6.5 µm pixel size) are often spatially binned during or post-acquisition ( Figure 5C). Image processing can be performed to generate activation and repolarization maps using custom algorithms 23,33,43,45 (Figure 3D), with the activation time of each pixel on the heart was defined as the maximum derivative of the action potential or calcium transient upstroke. Example of epicardial pacing at cycle length of 400 ms (S1−S1), which was used for imaging experiments.…”
Section: Representative Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, high spatial resolution images (in the described setup 1240 x 1024 total, or 620 x 512 per channel, 6.5 µm pixel size) are often spatially binned during or post-acquisition ( Figure 5C). Image processing can be performed to generate activation and repolarization maps using custom algorithms 23,33,43,45 (Figure 3D), with the activation time of each pixel on the heart was defined as the maximum derivative of the action potential or calcium transient upstroke. Example of epicardial pacing at cycle length of 400 ms (S1−S1), which was used for imaging experiments.…”
Section: Representative Resultsmentioning
confidence: 99%
“…6. After temporal parameters are calculated, generate isochronal maps to depict aspects of a single action potential or calcium transient across the entire imaged epicardial surface using custom algorithms23,33,43,45,46…”
mentioning
confidence: 99%
“…To further characterize the effect of phthalates on cardiac electrophysiology, our laboratory selected a dose of MEHP (60 μM) comparable to patient plasma levels after exchange transfusion for isolated, Langendorff‐perfused heart studies (Jaimes et al, 2019; Sjoberg et al, 1985). In this study, we observed that MEHP‐treatment slowed sinus node recovery time, increased atrioventricular conduction time, and slowed epicardial conduction velocity (Jaimes et al, 2019). Effects on conduction time may be partly attributed to inhibitory effects on voltage‐gated sodium channels, as voltage‐clamp studies in HEK 293 cells revealed a reduction in fast and late sodium current, albeit at relatively high MEHP concentrations (IC 50 874 and 231 μmol/L, respectively).…”
Section: Di‐2‐ethylhexyl Phthalatementioning
confidence: 99%
“…Although, it is important to note that both chemicals exert biological effects through multiple mechanisms of action. Once inside the body, bisphenol and phthalate chemicals may interact with nuclear receptors, hormone receptors, transcription factors, ion channels and disrupt intracellular signaling pathways (Ben‐Jonathan & Steinmetz, 1998; Ito, Kamijima, & Nakajima, 2019; Jaimes et al, 2019; La Merrill et al, 2020; MacKay & Abizaid, 2018; Mariana et al, 2016; Moriyama et al, 2002; Nadal et al, 2000; Rowdhwal & Chen, 2018; Singh & Li, 2012; Sohoni & Sumpter, 1998; Soriano et al, 2016; Wetherill et al, 2007; Ye et al, 2017). Many of these interactions can result in acute and rapid consequences.…”
Section: Introductionmentioning
confidence: 99%
“…Langendorff-perfused rat hearts were isolated and analyzed by electrophysiology experiments and optical mapping. The results showed that MEHP-treated hearts had slow atrioventricular conduction, increased atrioventricular and ventricular refractory periods, and also exhibited a triangulated action potential and a steeper electrical restitution curve [ 56 ]. These results confirm that DEHP and its metabolite MEHP are associated with the development of arrhythmias.…”
Section: Animal Studiesmentioning
confidence: 99%